Wage augmented stochastic frontier model with truncated normal distribution - Ferdushi, Kanis Fatama; Baten, Md Azizul; Kamil, Anton Abdulbasah; Mustafa, Adli (Academic Journals, 2011)
This study considered wage augmented production frontiers with inefficiency effects model proposed by Battese and Coelli (1992) where the efficiency wage hypotheses was tested.An unbalanced panel data on 31 manufacturing firm for the period 1989 to 2000 was used in this study.The wage augmented CobbDouglas production function was originated to be an unsatisfactory representation of the data compared to wage augmented Translog frontier model.The results showed that the wage level was one of the significant factors contributing to the output and technical efficiency in truncated normal distribution which was found to be of inferior quality in manufacturing industry in Bangladesh.